The Implementation of Policy on Granting Funds Based on Regulation of the Minister of Trade of the Republic of Indonesia No. 123 of 2018 concerning Guidelines for Granting Funds and Management Procedures Sourced from the Regional Budget at the Bureau of People's Welfare, Regional Secretariat of North Sumatra Province - Unawi, Rinda; Sinaga, Rudi Salam; Hartono, Budi (Budapest International Research and Critics University, 2021)
The aims of this study is to find out Implementation of Policy for Granting Funds Based on Permendagri No. 123 of 2018 concerning Guidelines for Granting Funds and Management Procedures Sourced from the Regional Budget at the Bureau of People's Welfare, Regional Secretariat of North Sumatra Province. This study used a qualitative approach. Based on the description of the research results that have been described in the previous chapter, the author draws conclusions in accordance with the problems studied regarding the Implementation of Giving Policy Grants Based on Permendagri No. 123 of 2018 concerning Guidelines for Granting Funds and Management Procedures Sourced from the Regional Budget at the People's Welfare Bureau of the Regional Secretariat of the Province of North Sumatra. The policy implementation process has been running in accordance with permendagri No. 123 of 2018 is still at the stage of making and submitting proposals. However, in its implementation towards perfection there are still obstacles, especially in the process of implementing policy implementation. These obstacles arise from internal and external factors in terms of several aspects, namely communication, resources, disposition, and the Bureaucratic Structure that still greatly influences the course of the policy implementation process. Among other things, there is still a lack of socialization and coordination in the sector in charge of the affairs of the grant aid fund. Whereas the coordination aims to determine the process of implementing grant assistance policies in the fields of Religion, Education and Institutions. Socialization and Coordination activities have not been carried out optimally so that the results are not optimal.Â